The Ccz1 mediates the autophagic clearance of damaged mitochondria in response to oxidative stress in Candida albicans. (December 2015) - Dong, Yijie; Yu, Qilin; Chen, Yulu; Xu, Ning; Zhao, Qiang; Jia, Chang; Zhang, Bing; Zhang, Kai; Zhang, Biao; Xing, Laijun; Li, Mingchun
Abstract: Autophagy plays a critical role in response to numerous cellular stresses, such as nutrient deprivation, hypoxia, starvation and organelle damage. The disruption of autophagy pathway affects multiple aspects of cellular stress response. Here we for the first time identified Ccz1 as an essential component for autophagy in Candida albicans . Our experiments demonstrated that loss of CCZ1 gene led to vacuolar fragmentation and disruption of the autophagy pathway. Our results also suggested that Ccz1 functioned in oxidative stress. In the ccz1 Δ/Δ mutant, the levels of reactive oxidative species (ROS) sharply increased under H2 O2 treatment. Further studies demonstrated that breakdown of the autophagic clearance pathway led to the accumulation of oxidative stress-damaged mitochondria, and consequently elevated cellular ROS levels in the ccz1 Δ/Δ mutant. Furthermore, deletion of CCZ1 led to a significant defect in filamentous development at both 30 °C and 37 °C. The disruption of CCZ1 gene led to decreased capacity of macrophage killing and increased sensitivity to the macrophages. In addition, the ccz1 Δ/Δ mutant exhibited attenuated virulence and decreased fungal burdens in the mouse systemic infection model, indicating that CCZ1 might provide a promising target for antifungal drugs development. In summary, our findings provide new insights into the understanding of autophagy-related gene in C. albicans .